ANALISIS KESULITAN PESERTA DIDIK DALAM MEMECAHKAN SOAL CERITA MATERI PECAHAN DI KELAS IV SD INPRES KARUNRUNG KOTA MAKASSAR - Dwi Nur Aledya, Vivi; Patta, Rahmawati; Pagarra, Hamzah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research uses a qualitative approach with a case study method. The purpose of the research is to analyze and describe the difficulties of students in solving story problems on fractions in grade IV. The subjects of this research are grade IV students of SD Inpres Karunrung who are grouped into 3 subjects. The selection of research subjects is based on the results of the test scores in solving story problems, namely, high, medium, and low scores, then one subject is selected for each subject to be the subject of research. Meanwhile, the object of research is the answer sheet of the results of the students' story problem solving test guided by interview guidelines. Data analysis uses the methods of data reduction, data presentation, data verification and conclusion drawing. The results of the study show that, of the five types of errors analyzed, errors in process skills and writing final answers are the most frequent types of errors and are experienced by all research subjects. Process skill errors are inaccuracies in performing fraction arithmetic operations, while errors in writing final answers occur because students do not conclude the results completely and correctly.